Moving towards inclusive learning and teaching: A synthesis of recent literature - Lawrie, Gwen; Marquis, Elizabeth; Fuller, Eddie; Newman, Tara; Qiu, Mei; Nomikoudis, Milton; Roelofs, Frits; van Dam, Lianne (Teaching and Learning Inquiry, 2017)
The need for inclusive and equitable approaches to teaching and learning is a persistent theme in recent literature. In spite of relatively widespread agreement about this objective, inclusion remains elusive, and opinions about how best to achieve it proliferate. To provide a landscape view of the field and offer recommendations for research and practice, this article provides a focussed review of literature connected to inclusive teaching and learning published since 2010. Drawing from a framework advanced by Hockings (2010), we synthesize key findings from recent scholarship and argue for the value of a whole-of-institution approach that considers the activities and interactions of educational actors operating at different institutional levels. We also extend this argument to consider the need for greater attention to factors that move beyond the individual institution and to advocate for further international research in particular.